The Influence of Social Media Marketing, Brand Awareness and Product Quality on Purchasing Decisions at Mie Djoetek - Ferdiana, Aprilisa Frincessa Syifa; Zulistiani, Zulistiani (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The purpose of this research is to analyze whether there is a significant influence between social media variables, brand awareness, and product quality simultaneously and partially on purchasing decisions at the Djoetek noodle shop. Design/Method/Approach: This research uses a quantitative approach and nonprobability sampling techniques. The population for this research is all customers who have purchased products at Kedai Mie Djoetek and the sample used in this research is 40 respondents who have made purchases at Mie Djoetek and analyzed using the classic assumption test, multiple linear regression method, coefficient of determination and hypothesis testing with SPSSv23 tools Research Findings: The results of this research are that social media marketing and brand awareness partially influence purchasing decisions at Mie Djoetek. Meanwhile, product quality has no partial effect on purchasing decisions. Simultaneously, social media marketing, brand awareness, and product quality have a significant influence Theoretical contribution/Originality: Social media marketing can expand understanding of how social media as a digital marketing platform influences consumer behavior and purchasing decisions. Measuring the impact and consumer preferences on brand awareness, and digging deeper into the concept of product quality from a consumer perspective influences purchases. Practitioner/Policy implications: This research provides practical implications for Mie Djoetek in improving purchasing decisions Research limitations: This research only discusses social media marketing and brand awareness as independent variables, and product quality as the dependent variable. Other variables still influence the dependent variable that need to be researched further